70=-5m+10

Simple and best practice solution for 70=-5m+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 70=-5m+10 equation:


Simplifying
70 = -5m + 10

Reorder the terms:
70 = 10 + -5m

Solving
70 = 10 + -5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5m' to each side of the equation.
70 + 5m = 10 + -5m + 5m

Combine like terms: -5m + 5m = 0
70 + 5m = 10 + 0
70 + 5m = 10

Add '-70' to each side of the equation.
70 + -70 + 5m = 10 + -70

Combine like terms: 70 + -70 = 0
0 + 5m = 10 + -70
5m = 10 + -70

Combine like terms: 10 + -70 = -60
5m = -60

Divide each side by '5'.
m = -12

Simplifying
m = -12

See similar equations:

| (13b-7)-4(3b+3)=-7 | | 8.2+(-3.5)= | | 3/6=x/10 | | -4(6+r)=-63 | | (x^4-y^4)(x^4+y^4)= | | 15=14-16.6m | | 10-9n-8n=-6(-6-9n)-4(11n-7) | | 38-5b=-3(-5-5b)+3b | | Y=x^12 | | 10/80=11/x | | 8=-7+5u | | 12=16y-28x | | -4(x+3)-7=29 | | 8x+4x+4+7=6x+3+5x | | x(4-3)=8x+2 | | 3t/3=5/3 | | m-5m+6=-3m+3 | | 2/3x-3=5/3x | | -7xy(4xy)= | | 88=4n+3n | | 1.5r+15=2 | | (2a-5)+(4-5)= | | -7-2=40 | | -15(-3)/-9= | | -3-y=1/5x | | -4875/-65= | | 12/5x=-18 | | x^2+8x=309 | | -4(2-3r)=-8-4(6-4r) | | 35-8m=-7(m-6) | | c*c=-5 | | 5/6/3/10 |

Equations solver categories